Tracing the Spatial Circulation of Yersinia pestis of Medieval Biovar in the Eastern Caspian Sea Region in the 20th Century Based on Genome-Wide SNP Analysis - G. A. Eroshenko; E. G. Oglodin; A. N. Balykova; Ya. M. Krasnov; E. A. Naryshkina; T. Z. Ayazbaev; N. V. Popov; V. V. Kutyrev (Проблемы особо опасных инфекций, 2022)
A comprehensive analysis of the accumulated epidemiological and epizootiological data in combination with results from phylogenetic analysis of Yersinia pestis strains creates the basis for establishing patterns of spatialtemporal distribution of the plague pathogen and opens up the prospect of long-term forecasting of natural plague foci activation. Previously, we traced the distribution pathways of Y. pestis, medieval biovar, in the plague foci of the Northern and Northwestern Caspian Sea regions in the 20th and early 21st centuries.The purpose of this work was to identify the regularities of circulation of Y. pestis, medieval biovar, in four natural plague foci located in the Eastern Caspian Sea region.Materials and methods. A complex study of the phenotypic and genetic properties of 16 Y. pestis strains isolated in the Ustyurt, Mangyshlak, Karakum and Kopetdag autonomous desert plague foci in 1926–1985 was carried out. They were compared with strains from other natural plague foci in Eastern Europe and Central Asia obtained in 1917–2003. Whole-genome sequencing of 12 of those strains was performed. Phylogenetic analysis included the genomes of other 19 Y. pestis strains that we had sequenced earlier. Based on the 1717 polymorphic nucleotides (SNPs) identified in the core genome, a dendrogram of the relations of the studied strains was constructed.Results and discussion. All 16 Y. pestis strains from the Ustyurt, Mangyshlak, Kopetdag, and Karakum desert foci belong to the 2.MED1 branch of the medieval biovar. All investigated strains from the first three foci and most of the strains from the Karakum focus are in the Caspian 2.MED1 branch, and three strains from the Karakum desert focus are included in the Central Asian one. We have revealed several waves of dissemination of the strains under the 2.MED1 phylogenetic branch of Y. pestis of the medieval biovar in the Eastern Caspian Sea region in the 20th century.